The Twilight of the Index - Trifonova, Temenuga (Cinema: Journal of Philosophy and the Moving Image, 2011)
The “digital turn” has prompted a renewed interest in the relationship between film and photography reflected in a return to questions of indexicality and a rethinking of medium specificity away from the idea of medium as a material or physical support. This paper explores the growing ambivalence surrounding the notion of indexicality as it manifests itself in contemporary “cinematic” photography (Barbara Probst, Uta Barth, and Jeff Wall), which, I argue, imposes a time of reading by means of self-reference that exposes a single moment’s difference from itself (Probst), by means of extending the present moment into a “long now” (Uta), or by means of enlarging the scale of the image and narrativizing it (Wall). “Cinematic” photography seeks to reclaim the cinematic within the photographic from within the twilight of indexicality: rather than putting us in a deep historical relation with time, it self-consciously reflects on indexicality, automatism, and duration.